Individual values and motivational complexities in ethical clothing consumption: a means-end approach - Thomas Jaegel; Kathy Keeling; Alexander E. Reppel; Thorsten Gruber (2012)
With the expansion of ethical consumption, there is an increased need to understand the variety of consumer motives for consumer engagement in such behaviour. For the rapidly growing area of ethical clothing, this study explores consumers' desired consumption outcomes and personal values that drive ethical product preferences. Analysis of data obtained through a semi-qualitative laddering approach (n = 98 ethical clothing consumers) reveals five dominant perceptual patterns relating not only to environmental and altruist ethical concerns, but also more individual motives of value for money, personal image, and well-being. Further analysis shows that consumers have to compromise and balance between their conflicting end-goals. The study augments previous findings in ethical clothing research, as researchers can better understand how specific attributes of products relate to the emotional and symbolic aspects and link back to consumer values. Though limited in scope by its exploratory character, the study contributes towards a deeper understanding of ethical consumer behaviour. Implications for theory practice and further research are discussed.